Benefits of Topical Avocado Oil in Improving Skin Moisture: A Study in Atopic Dermatitis Patients - Pramitasari, Yuniar Dian; Muslimin, Muslimin; Afriliana, Liza (RSUP Dr. Kariadi, 2026)
BACKGROUND : Atopic dermatitis is a chronic skin condition characterized by recurrent flare-ups that impair skin barrier function and significantly affect patients’ quality of life. One of the key strategies in managing atopic dermatitis is to strengthen and maintain the skin's barrier function while reducing inflammation commonly achieved through the use of moisturizers such as petrolatum. However, petrolatum has several drawbacks, including a thick consistency that makes it difficult to apply, a greasy and shiny appearance, and the potential to cause follicular occlusion. As an alternative, avocado oil offers promising benefits due to its non-comedogenic properties and non-greasy finish. AIM : To determine the difference in effectiveness between avocado oil and petrolatum in improving skin moisture. METHOD : This study is a single-blind randomized clinical trial using a two-parallel group pre- and post-test design. Samples were selected using consecutive sampling. The treatment was applied to the right and left forearms of patients with non flare-ups atopic dermatitis. RESULT : The variable of user complaints was statistically significant in the general characteristics, with a p-value of <0.05. The TEWL (Transepidermal Water Loss) score for topical avocado oil showed a significant difference compared to petrolatum, with a p-value of <0.001. CONCLUSION : A greater reduction in TEWL (indicating improved skin moisture) was observed with the application of 100% topical avocado oil in patients with non flare-ups atopic dermatitis, compared to the use of 100% topical petrolatum.